2014
DOI: 10.5455/ijmsph.2014.210220141
|View full text |Cite
|
Sign up to set email alerts
|

A genderwise study on the morphometry of infraorbital foramen and its laterally in dry adult skulls of South Indian population

Abstract: Background: The infraorbital foramen is situated in the maxilla and it conveys infraorbital nerve and vessel, the knowledge of its morphometry and variations is therefore mandatory to do therapeutic infraorbital nerve block or any clinical procedures. Aims & Objective: To study the gender wise morphometry of infraorbital foramen and its laterality in dry adult skulls of south Indian population. Materials and Methods: In the present study we examined 100 infraorbital foramina and measured its distance with bony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The values found for the distance from the IOF to the ANS in our study varied significantly between the sexes and between the sides of the maxilla. These findings were very similar to those described by Ekambaram et al [ 14 ] and Lopes et al [ 10 ]. However, the mean values found for this variable in the study of Ukoha et al [ 17 ] were smaller, which may be associated with anatomical differences between different ethnic groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The values found for the distance from the IOF to the ANS in our study varied significantly between the sexes and between the sides of the maxilla. These findings were very similar to those described by Ekambaram et al [ 14 ] and Lopes et al [ 10 ]. However, the mean values found for this variable in the study of Ukoha et al [ 17 ] were smaller, which may be associated with anatomical differences between different ethnic groups.…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of multiplicity of the IOF has been found to range from 4% to 11% [ 3 9 14 ]. In our study, multiplicity of the IOF was found in 10.7% of the crania studied, without any significant difference in relation to sex or the sides of the maxilla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also comparable to a Brazilian study by Chracanovic et al [11] and a study by Elsheikh et al [12] in the Egyptian population. Some south Indian studies showed values (> 7 mm) that were higher than ours [13,14]. Studies on African American skulls by Zang et al [15] and Nigerian skulls by Ukoha et al [16] also reported higher values.…”
Section: Discussionmentioning
confidence: 50%
“…One study was by Singh et al [9] in the North Indian population, and another by Przygocka et al [20] in the Polish population. On the contrary, a south Indian study by Ekambaram et al [13] reported values lower than 40 mm.…”
Section: Discussionmentioning
confidence: 83%